Transformasi Digital Marketing dan Dampaknya terhadap Customer Experience, Kepuasan, serta Loyalitas Pelanggan di Era Marketplace: Sebuah Kajian Konseptual pada Marketplace Digital - Siregar, Akhmad Irwansyah (Universitas Batanghari Jambi, 2025)
This study aims to explore the relationship between digital marketing, customer experience, customer satisfaction, and customer loyalty in the context of a digital marketplace. This study used a literature review method with a descriptive-analytical approach through a search of various relevant, up-to-date scientific sources, both from national and international journals. The results show that digital marketing plays a significant role in creating valuable customer experiences through easy access, two-way communication, and relevant content. Positive experiences subsequently increase satisfaction levels, which ultimately strengthen customer loyalty and repurchase intentions. This study confirms that digital transformation focuses not only on technology but also on understanding consumer behavior and integrative strategies oriented toward customer value.